Morphological variability of Cardaminopsis halleri (L.) Hayek from selected habitats in the Silesian Upland (Southern Poland) - Fiałkiewicz, Barbara; Rostański, Adam (Biodiversity: Research and Conservation, 2006)
Cardaminopsis halleri, a known hyperaccumulator, shows considerable morphological variability in the territories with a high level of heavy metal (Zn, Cd, Pb) pollution. Therefore, the presented studies were designed as an attempt to explain the scope and causes of observed variability. Plants from Cardaminopsis halleri populations was collected in the vegetation seasons of 2003 and 2004 in the vicinity of two sources of zinc and lead pollution and from two control localities. For each individual, 15 quantitative variables (traits) and 12 qualitative ones were analysed. Statistically significant differences were shown for qualitative and quantitative traits, attesting to high morphological variability between the investigated populations of Cardaminopsis halleri. Populations exposed to strong heavy metal pollution were characterised by significantly smaller size of rosette and stem leaves in comparison to control populations. Chromosome numbers of all individuals in the studied populations is the same (2n=16), which proves that the observed differences are not a result of polyploidy. The populations from Bieszczady (control localities) differ significantly from the populations from Silesia with regard to a number of qualitative and quantitative characteristics. High heavy metal pollution is one of important factors which influence the morphological variability of investigated Cardaminopsis halleri populations.